The Effect Of The Marketing Mix On Sales Rate At Ayam Keprabon Restaurant - Fakhry Adam Prayogo; Rayhan Gunaningrat; Indra Hastuti (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
In this study has the aim to determine the effect of marketing mix on sales levels at Ayam Keprabon Restaurant, using a sample size taken totaling 100 people from consumers of Ayam Keprabon Restaurant. The sampling technique uses purposive sampling, data is taken using a questionnaire measured by a Likert scale. This study used multiple linear regression analysis. At this time the marketing mix is the key to marketing in a company that can increase the level of sales. Based on the theoretical foundation and accompanied by the results of the analysis it can be concluded that, Food Quality has a significant effect on the Sales Level, Service Quality does not have a significant effect on Sales Level, Price has no significant effect on Sales Level, Physical efidence does not have a significant effect on Sales Level, Process does not have a significant effect on sales level, Place or Distribution Channel has a significant effect on sales level. Food quality, service quality, price, physical efidence, process and place together have a simultaneous effect on the variable Sales Level in Ayam Keprabon restaurant.